Angular analysis of the decay B0s → φe+e- - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2025)
An angular analysis of the decay Bs0 -> phi e+e- is presented, using proton-proton collision data collected with the LHCb detector between 2011 and 2018 at centre-of-mass energies of 7, 8 and 13 TeV. The combined dataset corresponds to an integrated luminosity of 9 fb-1. Observables are determined by fitting time-integrated projections of the angular distribution in three bins of dielectron mass squared, q2, corresponding to [0.1, 1.1], [1.1, 6.0] and [15.0, 19.0] GeV2/c4. The results are compatible with predictions based on the Standard Model of particle physics.